MOCDEX: Multiprocessor on Chip Multiobjective Design Space Exploration with Direct Execution. (12th October 2006) - Ben Mouhoub, Riad; Hammami, Omar
Abstract : Fully integrated system level design space exploration methodologies are essential to guarantee efficiency of future large scale system on programmable chip. Each design step in the design flow from system architecture to place and route represents an optimization problem. So far, different tools (computer architecture, design automation) are used to address each problem separately with at best estimation techniques from one level to another. This approach ignores the various and very diverse vertical relations between distinct levels parameters and provides at best local optimization solutions at each step. Due to the large scale of SoC, system level design methodologies need to tackle the system design process as a global optimization problem by fully integrating physical design in the design space exploration. We propose MOCDEX, a multiobjective design space exploration methodology, for multiprocessor on chip which closes the gap between these associated tools in a fully integrated approach and with hardware in the loop. A case study of a 4-way multiprocessor demonstrates the validity of our approach.